Evaluation of acute bronchodilator reversibility in patients with symptoms of GOLD stage I COPD. Issue 3 (3rd December 2008) - O'Donnell, D E; Laveneziana, P; Ora, J; Webb, K A; Lam, Y-M; Ofir, D
Abstract : Background: Patients with symptoms of GOLD stage I chronic obstructive pulmonary disease (COPD) can have significant abnormalities of ventilatory mechanics with greater exertional symptoms and exercise limitation than age-matched healthy subjects. In such patients the impact of bronchodilator therapy remains unknown and is difficult to evaluate. Methods: The acute effects of nebulised ipratropium bromide 500 μg (IB) on resting pulmonary function and on dyspnoea and ventilatory parameters during symptom-limited constant work rate cycle exercise were measured. In a randomised double-blind crossover study, 16 patients with COPD (mean (SD) post-bronchodilator forced expiratory volume in 1 s (FEV1 ) 90 (7)% predicted, FEV1 /forced vital capacity (FVC) 59 (7)%) with a significant smoking history (mean (SD) 44 (16) pack-years) inhaled either IB or placebo on each of two separate visits. Pulmonary function tests and cycle exercise at 80–85% of each subject's maximal work capacity were performed 2 h after dosing. Results: Compared with placebo, FEV1 increased 5 (9)% predicted, residual volume decreased 12 (20)% predicted and specific airway resistance decreased 81 (93)% predicted (all p<0.05) after IB. At a standardised time during exercise, dynamic inspiratory capacity and tidal volume significantly increased in tandem by 0.12 and 0.16 litres, respectively (each p<0.05), dyspnoea fell by 0.9 (1.8) Borg units (p = 0.07) and dyspnoea/ventilation ratios fell significantly (p<0.05). The fall in dyspnoea intensity at higher submaximal ventilations correlated with the concurrent decrease in end-expiratory lung volume (p<0.05). Conclusion: In patients with symptoms of GOLD stage I COPD, IB treatment is associated with modest but consistent improvements in airway function, operating lung volumes and dyspnoea intensity during exercise. These results provide a physiological rationale for a trial of bronchodilator therapy in selected patients with milder but symptomatic COPD.